1242. Quantitative Analysis of Microbial Burden on LTCF Environmental Surfaces. (26th November 2018) - DiBiase, Lauren; Powell, Amy; Gergen, Maria; Weber, David J; Sickbert-Bennett, Emily E; Rutala, William A
Abstract: Background: There is a lack of data on environmental surface contamination in long-term care facilities (LTCF), despite multiple reports of outbreaks of multi-drug-resistant organisms in these settings. Therefore, we conducted a quantitative analysis of the microbial burden and prevalence of epidemiologically important pathogens (EIP) found on LTCF environmental surfaces. Methods: Microbiological samples were collected using Rodac plates from resident rooms and common areas in five LTCFs. At each facility, five samples from up to 10 different available environmental surfaces were collected from a room of a resident reported to be colonized with EIP, as well as from a room of a resident reported to be non-colonized. In addition, five samples from up to 10 different environmental surfaces were collected from two common areas in the facility. EIPs were defined as MRSA, VRE, C. difficile and multi-drug-resistant Gram negative bacilli. Data were analyzed for each environmental site sampled in a resident room or common area based on total bacterial colony forming units (CFU), mean CFU per Rodac, total EIP by site, and mean EIP counts per Rodac. Results: The below table summarizes total EIP recovered from environmental sites by reported EIP colonization status of the resident. Rooms of residents with reported colonization had much greater EIP counts per Rodac (8.32, 95% CI 8.05, 8.60) than rooms of non-colonized residents (0.78, 95% CI 0.70, 0.86). MRSA was the most common EIP recovered from Rodacs, followed by C. difficile . Very few EIPs were recovered from the common areas sampled at these LTCFs. Conclusion: We found varying levels of CFU and EIP on environmental sites at LTCFs. Colonization status of a resident was a strong predictor of higher levels of EIP being recovered from his/her room. Disclosures: All authors: No reported disclosures.